A Fully Decentralized Web Application Framework with Dynamic Multi-Point Publishing and Shortest Access Path - Bin Yu; Yuhui Fan; Peng Zhao; Xiaoyan Li; Lei Chen (Information)
Decentralized applications (DApps) have found extensive use across various industries. However, they still face several issues that need to be resolved. Currently, DApps are in a semi-decentralized stage, as only partial decentralization has been achieved. This paper presents FDW, a fully decentralized web application framework, which mainly includes the DWeb market, developer client, publisher client, and visitor client. The DWeb (Decentralized Web) market is established to manage all DWebs. In the DWeb market, developers can register, upload, and maintain DWebs; publishers can download, validate, and deploy DWebs; and visitors can browse DWebs and provide content. To guarantee the reliable operation of DWebs, multiple publisher nodes deploy a DWeb through dynamic multi-point publishing. By adopting the shortest access path, client nodes can efficiently access any DWeb from the closest publishing node. Additionally, the incentive and governance mechanisms encourage collaboration among all participants, ensuring the security of FDW. A prototype system of FDW has been developed, which consists of a DWeb container and an example DWeb. An analysis and evaluation of the decentralization, scalability, and security of FDW are provided. Compared with other related schemes, FDW shows certain advantages in these aspects.